[Black speaker hoisting a framed print at the AASU podium] (1993)
The speaker is wearing a suit and a multi-colored bow tie, and the framed print depicts a person in ancient garb. The podium is for the Cal Poly S.L.O. African American Student Union (AASU). Three other Black people are behind him with papers in their hands.